Influence of pH adjustment on physicochemical properties of microfiltration retentates of skim milk and rehydration properties of resulting powders. (May 2021) - Panthi, Ram R.; Bot, Francesca; Shibu, Sini N.; Saladukha, Dzianis; Ochalski, Tomasz J.; O'Mahony, James A.
Abstract: Effects of pH adjustment on physicochemical properties of microfiltration retentates of skim milk and rehydration of resulting micellar casein concentrate (MCC) powders were investigated. Aliquots of retentate (pH 6.9) were adjusted to pH 7.3, 7.6 or 7.6 followed by readjustment to pH 6.9 (6.9R) prior to powder preparation. The retentates with pH 6.9, 7.3, and 7.6 had casein micelle size of 179, 189 and 197 nm, respectively, while sample 6.9R had size of 183 nm, similar to retentate at pH 6.9. Higher retentate pH resulted in lower ionic calcium and higher conductivity, with sample 6.9R having higher values for both parameters than the pH 6.9 sample. The MCC powders displayed poorer wettability and enhanced dispersibility with increasing retentate pH. Interestingly, the 6.9R powder had the best wettability and dispersibility. This study demonstrated that pH-mediated modifications of the physicochemical properties of retentates improve the rehydration properties of resultant MCC powders.